Solitary pancreatic head metastasis from tibial adamantinoma: a rare indication to pancreaticoduodenectomy. Issue 2 (13th February 2018) - Silvestri, S; Deiro, G; Sandrucci, S; Comandone, A; Molinaro, L; Chiusa, L; Fronda, G R; Franchello, A
Abstract: Pancreatic metastases are rare, <2% of all pancreatic neoplasia. This is the first case of pancreatic metastasis from adamantinoma, a rare, low grade and slow growing tumor which is frequently localized in long bones. We describe a case of a 45-year-old woman presenting with increased bilirubin level. Computed tomography and ecoendoscopic ultra sonography revealed a pancreatic head mass. Fine-needle aspiration biopsy was consistent with metastatic adamantinoma. The patient was submitted to a standard pancreaticoduodenectomy. As in the case presented, standard pancreatic resections are safe and feasible options to treat non-pancreatic primary tumor improving patient's survival and quality of life.